Differences in Normal Childbirth Assistance Skills between Model Media and Video Media - Sholikha, Siti; Puspita, Irma Maya; Handayani P, Dwi Imawati (Universitas Islam Lamongan, 2023)
The development of the current era demands quality human resources. One vehicle to improve the quality of human resources is education with various learning media. This research is a comparative analytic study with a cross sectional approach. The population consisted of 39 students, a sample of 32 students was selected by simple random sampling. The independent variables are media and video models, while the dependent variable is the skills of normal childbirth assistance. The results showed that 11 respondents (69%) had skills in the capable category, while respondents with video media had skills in the advanced category, namely 10 respondents (62%). Data analysis using SPSS with the Mann-Whitney test using = 0.05 obtained a value of p = 0.000 so that p <Î± in conclusion there are differences in delivery assistance skills with model and video media. Seeing these results, it is necessary to think about the use of media in accordance with learning objectives to increase learning motivation to improve skills.